2008
DOI: 10.1080/17453670810016641
|View full text |Cite
|
Sign up to set email alerts
|

Degree of corticosteroid treatment within the first 2 months of renal transplantation has a strong influence on the incidence of osteonecrosis of the femoral head

Abstract: Degree of corticosteroid treatment within the first 2 months of renal transplantation has a strong influence on the incidence of osteonecrosis of the femoral head, Acta Orthopaedica, 79:5, 631-636, DOI: 10.1080 Background and purpose It has been suggested that avascular osteonecrosis (AVN) of the femoral head develops early after renal transplantation. We evaluated the relationship between risk of AVN and dose of steroids administered in different time periods.Methods Development of AVN was determined using M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 21 publications
2
32
0
Order By: Relevance
“…The incidence of osteonecrosis of the femoral head (ONFH) has been on the rise in recent years due to the widespread use of steroid medication for immunosuppression, especially in transplant patients and in the treatment of rheumatic diseases [1][2][3]. However, the pathogenesis of steroidinduced ONFH has not yet been identified.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of osteonecrosis of the femoral head (ONFH) has been on the rise in recent years due to the widespread use of steroid medication for immunosuppression, especially in transplant patients and in the treatment of rheumatic diseases [1][2][3]. However, the pathogenesis of steroidinduced ONFH has not yet been identified.…”
Section: Introductionmentioning
confidence: 99%
“…MRI has been reported to have high sensitivity and specificity for the diagnosis of AVN (Sugano et al 1999), and should be used for precise assessment of AVN development. Only a few reports have used MRI to determine the risk of AVN development in the early period after renal transplantation; this includes studies that have shown statistically significant relationships (1) between AVN development and total dose of steroid within 2 months postoperatively (Shibatani et al 2008), and (2) between AVN development and delayed renal function (Takao et al 2011). …”
mentioning
confidence: 99%
“…Also is not clear whether the risk of ON is related to cumulative steroid dosage or not dose dependent. [1,[8][9][10][11][12] In the literature, some case series showed that corticosteroid associated ON could be related to individual response (e.g. changes in steroid metabolism, hypercoagulable, hypofibrinolysis and genetic factors).…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] In contrast, many different investigators suggest that steroidinduced osteonecrosis is dose dependent. [1,[11][12][13] In our liver transplantation center, steroid usually tapered in three to six months. However, our patient has a history of high dose steroid usage for a long time due to immune thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%